Intrinsic motivation, career exposure, and quality of life: How do they influence the accounting students’ career choice? - Saarce Elsye Hatane; Fenia Agustin Gunawan; Stella Wulan Pratama (Journal of Education and Learning (EduLearn), 2021)
This study aimed to determine the factors that are considered by accounting students who choose careers as public accountants and private accountants. Three factors that became the focus of observation are intrinsic motivation, career exposure, and quality of life. Data collection in this research was organized in several public and private universities in Java. The survey was distributed online and obtained 445 valid questionnaires used to test the research model. The findings indicated that students who have more career information are more likely to choose a career as a public accountant. Besides, students who have a higher perception of the quality of life tend to choose a career as a private accountant. This study has not found significant evidence on the effect of intrinsic motivation on career choice. This study promotes accounting career institutions and universities in developing the interest of the younger generation in the accounting profession, be it public accountants or private accountants. Developing from the limitations in this study, further research can develop this accountant career research model by considering other factors, as well as observing accounting students in various demographic variations.